Dynamics of ostracod populations from shallow lakes of Patagonia: life history insights - Coviaga, Corina Anabel (2015)
Wetlands are one of the most valuable natural resources, providing a number of ecosystem services and socio-economic values. Small ponds sustain a rich aquatic biodiversity and because of their short hydrological regimen and small size are excellent environments for population studies of microcrustaceans such as ostracods. This study describes the population dynamics of the Ostracoda fauna in three temporary shallow lakes during one hydroperiod in Argentine Patagonia. Three cosmopolitan species were determined: Cypris pubera, Tonnacypris lutaria and Eucypris virens. Among them, T. lutaria is here reported for the first time from the Neotropical region. Multivariate ordination techniques were used to examine the relationships among environmental variables and ostracod density on each sampling site. High values of conductivity, absorption at 320 nm (as a measure of dissolved organic matter), dissolved oxygen concentration, temperature and chlorophyll a concentration correlated positively with ostracod density. All the populations studied reproduced parthenogenetically, and the life cycles of E.virens and C. pubera were followed in detail by weekly sampling of their populations. The former displayed continuous reproduction, whereas the latter showed a multivoltine strategy. The life history of C. pubera was affected by the seasonality of the habitat. The development rate correlated positively with water temperature; conductivity and temperature had a positive effect on adult size in C. pubera, while conductivity had a negative effect on adult size in E. virens. In this study, we present the first data set on the development and life history of ostracods in Patagonian freshwater environments. However, several questions remain and encourage us to further investigate the relative importance of ostracods in food webs, as well as the importance of inter-specific interactions between ostracods and other taxa.